Development of Production Information System in a Plywood Company for Monitoring Production Duration Process - Aziiza, Arizia Aulia; Chandra, Aaron Macauley; Prijambodo, Bambang; Absari, Dhiani Tresna (Journal of Digital Business and Innovation Management, 2025)
Production activities in manufacturing companies are essential elements of the company. Recording production activities must be documented to produce information needed to make the right decisions in production and use of all existing company resources. This study focuses on developing a Production Information System in a plywood company. The company's production planning activities and monitoring are documented using Excel. This causes difficulties in monitoring the duration of production activities carried out. This study aims to develop a production information system that monitors production processes. This system includes raw material procurement, production planning, inventory control, and production process monitoring. The development methods include production process analysis, data collection, cost calculation method research, system design, implementation, testing, and evaluation. The verification process is carried out by checking all features and the progress of the production process. The validation process is carried out by interviewing and testing the system on users. As a result, the system has been able to meet company standards in managing production routing based on the duration calculations prepared so that the PPIC manager can monitor the progress of ongoing production.